2014
DOI: 10.1038/modpathol.2014.34
|View full text |Cite
|
Sign up to set email alerts
|

NFκB expression is a feature of both activated B-cell-like and germinal center B-cell-like subtypes of diffuse large B-cell lymphoma

Abstract: The activation of nuclear factor kappa B (NFjB) transcription factor family is considered to have a key role in diffuse large B-cell lymphoma (DLBCL) pathogenesis and is associated with a specific molecular subtype, the activated B-cell-like (ABC) subtype. We evaluated the expression of NFjB by immunohistochemistry in a large series of DLBCL cases. The five different NFjB family members (NFjB1, NFjB2, RELA, RELB, and REL) showed a heterogeneous expression pattern with the vast majority of cases being positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
4
22
2
Order By: Relevance
“…These data are similar to that reported by Odqvist and Co-workers 16 who used similar cutoffs, except that the expression frequency of class II molecules showed significant differences. The variations might have resulted from a difference in the fixation procedure because we used identical antibodies (p50, rabbit polyclonal antibody (GeneTex, Irvine, CA, USA); p52, mouse monoclonal antibody (Millipore, Billerica, MA, USA); p65, mouse monoclonal antibody (Santa Cruz biotechnology, Santa Cruz, CA, USA); RELB, rabbit polyclonal antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA); and c-Rel, rabbit polyclonal antibody (Calbiochem, Darmstadt, Germany)) to those used by Odqvist et al 16 With a cutoff value of 30%, Compagno et al showed that about 30% of GCB-DLBCL and 60% of ABC-DLBCL had nuclear expression of NF-κB subunits (either p50 or p52) by immunohistochemistry using rabbit monoclonal antibodies (Cell Signaling Technology, Danvers, MA, USA). 8 In our cohort, 36% of GCB-DLBCL and 43% of ABC-DLBCL expressed either p50 or p52, which are similar to their results in GCB-DLBCL (30%) but slightly lower in ABC-DLBCL (43%).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These data are similar to that reported by Odqvist and Co-workers 16 who used similar cutoffs, except that the expression frequency of class II molecules showed significant differences. The variations might have resulted from a difference in the fixation procedure because we used identical antibodies (p50, rabbit polyclonal antibody (GeneTex, Irvine, CA, USA); p52, mouse monoclonal antibody (Millipore, Billerica, MA, USA); p65, mouse monoclonal antibody (Santa Cruz biotechnology, Santa Cruz, CA, USA); RELB, rabbit polyclonal antibody (Santa Cruz Biotechnology, Santa Cruz, CA, USA); and c-Rel, rabbit polyclonal antibody (Calbiochem, Darmstadt, Germany)) to those used by Odqvist et al 16 With a cutoff value of 30%, Compagno et al showed that about 30% of GCB-DLBCL and 60% of ABC-DLBCL had nuclear expression of NF-κB subunits (either p50 or p52) by immunohistochemistry using rabbit monoclonal antibodies (Cell Signaling Technology, Danvers, MA, USA). 8 In our cohort, 36% of GCB-DLBCL and 43% of ABC-DLBCL expressed either p50 or p52, which are similar to their results in GCB-DLBCL (30%) but slightly lower in ABC-DLBCL (43%).…”
Section: Discussionsupporting
confidence: 90%
“…Although constitutive activation of NF-κB is a hallmark of ABC-DLBCL, several groups have shown that NF-κB is also activated in a subset of GCB NF-κB subunits and clinical outcome in DLBCL DLBCLs. 8,10,16 Our data, combined with others, suggests that activation of the NF-κB pathway is not limited to ABC-DLBCL. We also found 23 cases with coexpression of p50 and p52, suggesting that activation of the classical and alternative pathways are not mutually exclusive in DLBCL.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations